Design‐driven resilience and the limits of geographic critique. Issue 2 (29th March 2022) - Cox, Savannah; Grove, Kevin; Barnett, Allain
Abstract: In April of 2019, the Rockefeller Foundation's '100 Resilient Cities' (100RC) programme abruptly shuttered, surprising programme proponents and critics alike. In this paper, we explore why this happened, why some styles of geographic critique could not anticipate 100RC's closure, and what this inability means for dominant strands of critical geographic analysis. To answer these questions, we bring literature on the biopolitics of resilience, technopolitics and Black geographies to bear on the case of Greater Miami resilience planning. We argue that answers to these questions revolve around the designerly roots of resilience thinking, whose distinct intellectual lineage conventional critical approaches have struggled to pick up on. We show how, on the one hand, design practices of synthesis in Greater Miami attempted to frame and instrumentalise Black histories of and experiences with racial and environmental violence as bounded knowledge that could improve the functioning of complex systems. On the other hand, synthesis created overflowings: opaque knowledges and experiences that resist the framing process and continue to mediate political battles over what resilience in Greater Miami practically becomes. Based on the case, we propose that an inductive style of critique that traces processes of framing and overflowing can help advance critical geographic analysis. As we illustrate in the paper, this mode of critique pays specific attention to the opaque, historically and contextually specific knowledges and experiences that refuse to be framed or synthesised, and work to counter‐frame dominant conceptions of resilience—critical and conventional alike. Abstract : Why did so many critical geographical scholars fail to anticipate the shuttering of 100 Resilient Cities, and what can this tell us about the limits of geographic critique? Bringing literatures in Black geographies, technopolitics, and biopolitics to bear on the case of Greater Miami resilience planning, we suggest new forms of critique that pay attention to processes of framing and overflowing can help push critical geographic scholarship in novel directions.